TECHNOLOGY OF PROTEIN FISH CONCENTRATE PRODUCTION (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
This article presents the results of research focused on developing a production technology for protein fish concentrate from Black Sea sand smelt (Atherina pontica), a widely available and nutritionally valuable small pelagic species in the Black Sea basin. The relevance of the study lies in addressing the need to enhance Ukraine’s food security by ensuring the rational and efficient utilization of domestic aquatic bioresources, particularly underutilized fish raw materials. The study involved an analysis of the physico-chemical composition of the raw material, including moisture, protein, and ash content, determined in accordance with national standards.A step-by-step technological scheme for producing fish concentrate is proposed, consisting of three subsystems: raw material preparation (defrosting, mechanical processing, gutting, washing, and mincing), drying (at 50, 70, and 100 °C), and final processing (grinding, sieving, pasteurization, and packaging). The drying kinetics were studied, and the influence of temperature regimes on moisture loss rate, residual protein content, and the sensory and technological qualities of the finished product was assessed. It was found that drying at 70 °C is optimal in terms of energy efficiency and preservation of protein functionality.The rehydration properties of the dried product were evaluated at different water temperatures. It was shown that concentrates dried at 50 and 70 °C exhibited higher water absorption coefficients than those dried at 100 °C, which is attributed to a lower degree of protein denaturation at lower drying temperatures. These findings highlight the potential of using Black Sea sand smelt as a high-protein ingredient in culinary and foodservice applications.Thus, the developed technology enables effective utilization of low-value fish raw materials, expands the range of protein-rich food products, reduces waste, and enhances the nutritional value of dishes based on natural protein components.
Keywords: Fish raw material; Atherina pontica; mince; drying; kinetics